TEACHER METHODS IN IMPLANTING RELIGIOUS AND MORAL VALUES OF EARLY CHILDHOOD IN SURAKARTA CITY - Wardani, Anita; Apriliani, Elina Intan; Ilmi Azizah, Annafi Nurul; Maryati, Sri (Journal of Educational Review and Research, 2023)
In order for students to have good religious and moral values, cultivation of moral and religious values is very important given from early so that when students move into higher levels already have the knowledge and experience that they gained at the time of preschool age. This study aims to find out the methods of teachers in instilling religious and moral values in early childhood at kindergarten in the city of Surakarta. This research is a qualitative descriptive study involving 10 teachers of kindergarten in the city of Surakarta. Data analysis uses descripative qualitational analysis that includes data reduction, data display, and conclusion drawings. The results of the research showed that the methods of teachers in instilling religious and moral values in early childhood in the kindergarten in the city of Surakarta have been very good, effective and performed optimally. The teacher's method of instilling religious and moral values in early childhood is by telling stories, demonstrating, practicing, playing and singing.